2018
DOI: 10.1080/13685538.2018.1482866
|View full text |Cite
|
Sign up to set email alerts
|

Consequences on aging process and human wellness of generation of nitrogen and oxygen species during strenuous exercise

Abstract: Impairment of antioxidant defense system and increase in metabolic rate and production of reactive oxygen species have been demonstrated in strenuous exercise. Both at rest and during contractile activity, skeletal muscle generates a very complex set of reactive nitrogen and oxygen species; the main generated are superoxide and nitric oxide. The nature of the contractile activity influences the pattern and the magnitude of this reactive oxygen and nitrogen species (ROS) generation. The intracellular pro-oxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 99 publications
1
13
1
Order By: Relevance
“…This finding seems to be in contrast with data reported elsewhere (29). However, it is necessary to take into account the great intra and interindividual variability of these parameters also in consideration of confounding factors, such as, for example, the use of supplements with antioxidant properties so widespread in our society (33). Furthermore, it should be noted that men enrolled in this study had an average age of 35.1 ± 8.2 years with an age range of 18-55 years, therefore younger than the studies that showed an increase in oxidative stress over time (29).…”
Section: Discussioncontrasting
confidence: 74%
“…This finding seems to be in contrast with data reported elsewhere (29). However, it is necessary to take into account the great intra and interindividual variability of these parameters also in consideration of confounding factors, such as, for example, the use of supplements with antioxidant properties so widespread in our society (33). Furthermore, it should be noted that men enrolled in this study had an average age of 35.1 ± 8.2 years with an age range of 18-55 years, therefore younger than the studies that showed an increase in oxidative stress over time (29).…”
Section: Discussioncontrasting
confidence: 74%
“…Recent studies in lean subjects have provided inconsistent evidence, reporting both unchanged and increased Adiponectin levels after exercise. Nevertheless, it was demonstrated that Adiponectin has anti-diabetic, antiatherogenic, anti-inflammatory and insulinsensitizing properties (Weyer et al, 2001;Abbasi et al, 2004;Bastard et al, 2006;Sessa et al, 2019). Therefore, the identification of different strategies such as physical activity able to up-regulate the expression of Adiponectin and/or to enhance the action of Adiponectin could strongly contribute to mitigate or minimize metabolic dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this design suggests several clinical research perspectives. In the next studies it will be interesting to evaluate if there are different levels of oxidative stress [43] capable of interfering on the validation of this equation and contextually evaluate the correlation with the quality of sexual activity [44], as well as compare aerobic exercise patterns vs other types of exercise.…”
Section: Discussionmentioning
confidence: 99%